Effects of Nordic hamstring exercise set configuration on eccentric hamstring strength changes in youth female athletes - Bounias, T.; Henry, G.; Goswami, R.; Moran, J.; Behm, D. G.; Drury, B. (The Journal of Strength and Conditioning Research, 2025)
Anterior cruciate ligament injury poses a significant risk in youth female athletes. The Nordic hamstring exercise (NHE) can improve eccentric hamstring strength (EHS), a key factor related to anterior cruciate ligament injury risk, yet limited research exists in this population. This study compared 2 NHE set configurations—traditional sets (TS) and rest redistribution (RR)—on EHS in youth female athletes. Subjects (age: 13.93 ± 1.58 years; body mass: 48.95 kg ± 11.15 kg; percentage of predicted adult height: 96.50% ± 4.30%) were randomly assigned to TS (n = 17) or RR (n = 18) groups. Both groups performed a 6-week NHE program, increasing weekly volume from 6 to 18 repetitions. Pretests and post-tests assessed EHS changes using the NordBord and isokinetic testing at 60°·s-1 and 180°·s-1, assessing peak torque (PT), angle of peak torque (°PT), and torque at 20°, 40°, 60°, and 80° of knee flexion. Both TS and RR significantly increased NordBord EHS (g = 0.34-0.98). Isokinetic data at 60°·s-1 and 180°·s-1 revealed significant small increases in PT and torque at 40°, 60°, and 80° (g = 0.22-0.46). Yet, no changes were observed in torque at 20° (g = 0.01-0.23) and the °PT increased (g = 0.33-0.83). No between-group differences were observed for any measure. These findings suggest that TS or RR set configurations can effectively enhance EHS in youth female athletes. However, to target EHS at longer muscle lengths, practitioners should include additional exercises beyond the NHE.